Causes, complications, and treatment of open ankle fracture - Sunbol, Khalid Mohammed; Alsulami, Salman Nawaf; AlSharif, Abdullah Mahfouz; Alshammari, Dhari Atallah; Alshehri, Mohammed Fadhel; Abu Alsaud, Sajidah Hisham; Alkhoshiban, Shaya Khoshiban; Alghamdi, Abdullah Saleh; Almohisin, Emad Ali; Alabbas, Fahad Mansour; Al Ghamdi, Razan Nasser (International Journal Of Community Medicine And Public Health, 2022)
Open ankle fractures are uncommon (3-6%) among all ankle fractures. Emerging trends show that the incidence of low-energy open ankle fractures is prevalent in older women. The mechanism of open fracture management continues to pose difficulties for orthopaedic surgeons. A simple fall is responsible for just under half of all fractures caused by motor vehicle collisions (MVCs). Despite technological advancements and surgical methods, infectious and non-infectious rates remain problematic. The mainstay of care is to combine antibiotic therapy with thorough irrigation and debridement. To prevent additional soft tissue and vascular damage, these fractures must be stabilized immediately, preferably with an external fixator. When the residual infection has cleared and the soft tissue envelope is adequate, do a definitive open reduction and internal fixation, adapting the procedure to the patient and type of fracture. Functional outcomes could be enhanced by taking safeguards against preventable comorbidities to reduce postoperative complications.